Histological Assessment of Early Bone-Response to ZrO2 Implant Accompanied by CaSO4.0.5H2O as a Bone Substitute - Ghufran Muslim Al-Banaa; Muhammed Salih Sulaiman; Abdulsattar Salim Mahmood (University of Mosul, College of Dentistry, 2021)
Aims: The study aims to assess the early bone response to a digitally designed and manufactured zirconia dioxide (ZrO2) implant accompanied by Calcium sulfate hemihydrate (CSH) as a bone substitute material. Materials and methods: Twenty rabbits were subjected to a surgical experiment to implant forty machined ZrO2 screws on their left femur bones. Each of the first twenty ZrO2 screws was fixated in the prepared implant cavity about 1cm away from the mesial femoral head of each rabbit, those were the group of (ZrO2). The other twenty implant cavities were prepared about 1cm away from each distal head and filled with a standard amount of CSH, then the remaining twenty ZrO2 screws were fixed, those were the group of (ZrO2+CSH). The bone response was evaluated histologically in intervals of 3, 7, 14, and 21 days where every 5 animals represent one interval. The histometric evaluation of the decalcified sections of the bone around each implant was done using a light microscope for the No. of osteoblast and osteocytes together with the bone trabecular thickness. Results: Significant differences were noted between both groups at all time-intervals regarding the number of osteocytes, and at each of 3, 7, and 14 days regarding the number of osteoblast, and at 3 and 7 days regarding the bone trabecular thickness. Conclusions: Within the limitation of this study we can conclude that the use of CSH as an artificial bone substitute around the ZrO2 implant can increase bone formation around the implant.